Soil Moisture Induced Genotype-by-Environment Interaction for Root Volume of Upland Rice - Nassir, Adesola Lateef; Adewusi, Kayode Matthew; Olagunju, Solomon O (Journal of Agricultural Sciences (Belgrade), 2018)
Sixteen rice genotypes comprising established cultivars, recent releases and breeding lines were established in the greenhouse under different moisture levels, obtained from a combination of amount and number of times of moisture application to study genotype-by-environment (GE) of root volume (RV) and also probe into the level of moisture imposition that would be adequate for screening of genotypes for response to moisture stress. Across the simulated environments, WAB 880-9-32-1-1-12-HB (G1) had the most root volume of 8.71cm3 while ITA 257 had the least (4.89cm3). Genotypes (G) accounted for a significant 10.6% of the total sum of squares with environment (E) and GE capturing equally significant 79.5 and 10.4 percent respectively. The GGE biplot clustered the environments into two groups with ITA 321 (G9) being the best for RV in environment E2 (100% moisture applied once a week), E5 (75% moisture applied twice per week) and E10 cluster (rainfed). WAB 880-9-32-1-1-12-HB (G1) recorded the best RV under environments with limited moisture but was also less stable and recorded grain production (13.5g/plant) close to the highest mean from ITA 150 (G3) (16.0g/plant) and IRAT 170 (G15) (14.1g/plant). Environments were generally positively correlated with vegetative and yield traits but E2, E5; E7, E8, E9 (50% of requirement) and E10 are highly discriminating and would be appropriate for discarding genotypes with poor RV. E1, E3, E4 and E6 were more representative of variable moisture condition and appropriate for selection of genotypes for RV within the overall goal of developing drought tolerant rice.